Control and Filtering of Fuzzy Systems Under Communication Channels - Chang, Xiao-Heng; Xiong, Jun; Li, Zhi-Min; Wu, Bo (Springer Nature Singapore : Imprint: Springer, 2023)
XI, 250 p. 81 illus., 78 illus. in color.